Acute Effect of Aliskiren on Smoking-Induced Endothelial Dysfunction in Smoker - Adam Uchida, Haruhito; Uchida, Hatsuzo; Wada, Jun (Journal of Cardiovascular Medicine and Cardiology, 2014)
Background: We aimed to examine the acute effect of aliskiren on smoking-induced endothelial dysfunction in smoker. Methods: Nineteen male smokers were enrolled. After all participants smoked a cigarette, their endothelial function was assessed with brachial artery flow mediated dilation (FMD). An hour after the administration of aliskiren, they smoked again, their FMD was assessed again. A month later, all measurements were performed again without the administration of aliskiren as a control. Blood pressure, plasma renin activity, and serum interleukin-6 concentration were also examined at the same time of FMD measurement. Results: A cigarette smoking led to an acute endothelial dysfunction (6.5 ± 1.7% to 3.4 ± 1.0 %, P = 0.02). Aliskiren administration significantly suppressed blood pressure and plasma renin activity, furthermore, improved FMD (6.7 ± 0.5% to 8.1 ± 0.8 %, P = 0.03). Aliskiren significantly reduced serum interleukin-6 concentration, but not in control. Conclusion: Aliskiren has a beneficial effect on smoking-induced acute endothelial dysfunction.